Luminosity from thermal neutron counting with MPX detectors and relation to ATLAS reference luminosity at √s= 8 TeV proton-proton collisions. (11th September 2017) - Sopczak, A.; Ali, B.; Asbah, N.; Bergmann, B.; Bekhouche, K.; Caforio, D.; Campbell, M.; Heijne, E.; Leroy, C.; Lipniacka, A.; Nessi, M.; Pospíšil, S.; et al.
Abstract: A luminosity determination based on thermal neutron counting with six MPX silicon pixel devices installed in the ATLAS cavern is presented. Recently, the ATLAS Collaboration published final\sqrt{s}=8 √ s =8 TeV luminosity results. This made possible to perform a detailed comparison and verify the potential of the thermal neutron counting as a novel method for luminosity measurements to supplement the well-established presently used procedures. This measurement is unique to the MPX network and has the advantage that the neutrons, which pass the MPX devices, cannot result from activation processes of material nearby. Good agreement is found between the MPX neutron counting results and the ATLAS reference luminosity. The differences between the ATLAS and MPX luminosity measurements are described by a Gaussian distribution with width of 1.5%.